Pengaruh Standar Akuntansi Pemerintah, Kompetensi Sumber Daya Manusia, Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kota Tidore Kepulauan - Rajak, Hasnawati Abd.; Hasan, Muhammad Hi; Yunus, Imran Hi (Peneliti.net, 2025)
This study aims to examine the Influence of Government Accounting Standards, Human Resource Competence, and Internal Control Systems on the Quality of Local Government Financial Reports. This type of research uses a quantitative approach, with a sample consisting of 78 respondents and the sampling technique employed is Purposive Sampling, which includes employees in the finance/accounting department and heads of agencies/SIPD operators in 39 Regional Apparatus Organizations (OPD) of Tidore Islands City. The results of the study show that: (1) The Government Accounting Standards variable partially has a positive and significant effect on the quality of financial statements, as evidenced by a t-value of 6.825 > t-table 1.992 and a significance value of 0.000 < 0.05. (2) The Human Resources Competence variable partially has a positive and significant effect on the quality of financial statements, as evidenced by a t-value of 2.864 > t-table 1.992 and a significance value of 0.005 < 0.05. (3) The Internal Control System variable partially has a positive and significant effect on the quality of financial statements, as evidenced by a t-value of 7.202 > t-table 1.992 and a significance value of 0.000 < 0.05. (4) Simultaneously, the variables of Government Accounting Standards, Human Resources Competence, and Internal Control System have a positive and significant effect on the quality of financial statements, as evidenced by an F-value of 194.787 > F-table 2.728 and a significance value of 0.000 < 0.05.